A follow-up study of 100 patients with acute brucellosis for its prognosis and prevention - Bai, Long; Ta, Na; Zhao, Aoning; Muren, Huhe; Li, Xueyong; Wang, Buhe Chaolu; Bagen, Hurile; Wen, Yongjun (Frontiers in Medicine, 2023)
Objective To prevent chronic brucellosis, this study analysed the changes in patient antibody titers, and the trajectories of biochemical indicators at different stages of brucellosis, identified relevant biomarkers, and explored risk factors affecting the prognosis of brucellosis patients. Methods A prospective cohort study was conducted to follow 100 patients with acute brucellosis. Laboratory serological test results [taken with a serum (tube) agglutination test (SAT)] and biochemical parameters (liver function, renal function, and hematological system) were measured repeatedly at four-time points: 0 weeks—baseline survey, 6 weeks after the first treatment, 12 weeks after the second treatment, and 3 months after the third treatment. The changes in the antibody titres and biochemical parameters at each time point were analysed for trend changes. Results One hundred patients with acute brucellosis were enrolled in this follow-up study, with 100% retention in follow-up. By the third follow-up, 21 patients had turned subacute and 11 had turned chronic. One-way repeated measures analysis of variance results showed statistically significant differences (p < 0.01) across the time points for the following five indicators: alanine aminotransferase, aspartate aminotransferase, total bilirubin, serum creatinine (SCr) and platelet count. The clinical symptoms of patients in the acute stage were mainly joint pain, fatigue, and fever, while those in the chronic stage complained primarily of joint pain and fatigue. The results of multivariate logistic analysis showed that joint pain [odds ratio (OR) = 3.652, 95% confidence interval (CI) =1.379–9.672], monoarticular pain (OR = 6.356, 95% CI = 4.660–8.669), elevated SCr (OR = 15.804, 95% CI = 1.644–151.966) and elevated haemoglobin (Hb) (OR = 1.219, 95% CI = 1.065–1.736) were risk factors for poor prognosis (not cured or chronic) in patients with brucellosis. Conclusion The trajectory of changes in patient SAT posirates and antibody titers can be used to distinguish patients with chronic brucellosis. The brucellosis is preventable and treatable, and the standard treatment can be effective in reducing the clinical symptoms of affected patients. If patients are not treated in a timely manner, joint pain, monoarticular pain, and elevated SCr are risk factors for patients who are not cured. Therefore, the treatment cycle for these patients should be extended.